Pengaruh Kapasitas Operasi, Arus Kas Operasi, Pertumbuhan Penjualan, dan Ukuran Perusahaan Terhadap Financial Distress - Salwa Aulia Hakim; Nurmadi Harsa Sumarta Sumarta (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2026)
The instability observed in the retail sector following the pandemic necessitates a thorough assessment of corporate financial endurance. This research examines how operating capacity, operating cash flow, sales trajectories, and firm size influence the likelihood of financial distress. Adopting a quantitative methodology, the study focuses on retail subsector entities on the Indonesia Stock Exchange from 2020 to 2024. Using a purposive sampling technique, 165 data points from 33 companies were evaluated via logistic regression. The findings reveal that operating capacity exerts a significant positive influence on financial distress, suggesting that asset growth without effective sales conversion intensifies bankruptcy threats. In contrast, operating cash flow, sales expansion, and company size function as significant risk mitigators. The study concludes that the survival of retail enterprises amidst economic shifts is fundamentally determined by asset management precision and robust cash liquidity